Disinfecting Handheld Devices And Objects With Uv-C In A Public Setting - V. Manoj Kumar, E. Vijayaragavan, T.A. Gowtham, Lolla Aditya Srivatsav, G. S. Jeyaram, K.Geethik (International Journal of Modern Agriculture, 2021)
In public many people are using handheld objects without any cleaning in which spread of germs takes place in the people. The primary objective is to kill the germs on handheld objects. People who use mobile devices and items during their everyday activities are included in the future before-and-after analysis. The fabrication of disinfector device is done with the help of E-waste. It has features like 3600 disinfection, automatic flip over and touch free mechanism. To implement these feature IOT devices, sensors and software were used. Handheld devices and objects underwent two 120-second UV-C disinfection cycles. To evaluate germicidal growth, samples are taken before and after a UV-C disinfection cycle. Swabs are tested in both pre UV-C exposure and post UV-C exposure. Once after the UVC test, it is observed that the percentage of germs is very less in handheld devices and objects. Ultra Violet-C appears to be effective at killing germs on handheld objects. It is operated automatically and touch free from start to the end. It is an effective disinfection device in a public setting.